Glycaemic effects of betel nut chewing in Type 2 Diabetes Mellitus - Tulo, Stella Tilu (Curtin University, 2014)
This research sought to access the effects of betel nut chewing on glycaemic control amongst patients with type 2 diabetes mellitus in Papua New Guinea. Whilst there were no observable acute effects of betel nut chewing on capillary blood glucose levels, a negative association was observed between betel nut use and glycaemic control in patients with long-term diabetes. Furthermore, betel nut consumption had a negative association with body mass index (BMI) and waist circumference.